(untitled) (Educator Insights: Journal of Teaching Theory and Practice, 2025)
This article highlights the pedagogical and psychological significance of the formation of students’ ability to think creatively. At the same time, the pedagogical aspects of the development of students’ creative competence are: the purpose of learning, the content of learning, teaching methods, the educational environment, the role of the teacher, the psychological aspects of the development of students’ creative competence: motivation, cognitive processes, personality traits, socio-psychological factors, the pedagogical aspect of students’ creative competence, the development of creative competence in the personal and pedagogical aspect: directed education, problem-based learning approach, interactive and collaborative learning, interdisciplinary integration, The psychological aspect of students’ creative competence, motivation and creative freedom, the development of divergent and convergent thinking, emotional intelligence and creativity, and the pedagogical and psychological significance of developing students’ creative competence are explained.